Analysis of Swamp Buffalo Tourism Potential to Improve Community Welfare in Paharangan Village, South Kalimantan - Huda, Isra Ul; Karsudjono, Anthonius Junianto; Sugiarto, Sugiarto (Raudhah Publisher, 2025)
This study explores the potential of swamp buffalo tourism in Paharangan Village, South Kalimantan, as a means to improve community welfare. By examining the cultural and economic value of swamp buffalo, the study highlights how community-based tourism could enhance local livelihoods and support sustainable development. Using interviews, observations, and SWOT analysis, findings reveal that swamp buffalo tourism has strong potential due to the cultural uniqueness of the buffalo and the village’s natural setting, despite challenges such as limited infrastructure and marketing support. Opportunities lie in the growing interest in eco-tourism and cultural experiences, which could position Paharangan as a distinctive destination. The study recommends a community-based model for tourism development, involving locals directly in planning, training, and promotional activities, thus enabling economic benefits and preserving cultural heritage. This research underscores the role of community-driven tourism in enhancing rural welfare and sustaining traditional practices in alignment with environmental conservation goals.